Bipartite Medial Cuneiform: Case Report and Retrospective Review of 1000 Magnetic Resonance (MR) Imaging Studies - Geraldine H. Chang; Eric Y. Chang; Christine B. Chung; Donald L. Resnick (Case Reports in Medicine)
Objective. To present a unique case report of a Lisfranc fracture in a patient with a bipartite medial cuneiform and to evaluate the prevalence of the bipartite medial cuneiform in a retrospective review of 1000 magnetic resonance (MR) imaging studies of the foot. Materials and Methods. Case report followed by a retrospective review of 1000 MR imaging studies of the foot for the presence or absence of a bipartite medial cuneiform. Results. The incidence of the bipartite medial cuneiform is 0.1%. Conclusion. A bipartite medial cuneiform is a rare finding but one with both clinical and surgical implications.